A three-dimensional analysis of overarm throwing in experienced handball players - van den Tillaar, R.; Ettema, G. (Journal of Applied Biomechanics, 2007)
The aim of this study was to investigate the contribution of upper extremity, trunk, and lower extremity movements in overarm throwing in team handball. In total, 11 joint movements during the throw were analyzed. The analysis consists of maximal angles, angles at ball release, and maximal angular velocities of the joint movements and their timing during the throw. Only the elbow angle (extension movement range) and the level of internal rotation velocity of the shoulder at ball release showed a significant relationship with the throwing performance. Also, a significant correlation was found for the timing of the maximal pelvis angle with ball velocity, indicating that better throwers started to rotate their pelvis forward earlier during the throw. No other significant correlations were found, indicating that the role of the trunk and lower limb are of minor importance for team handball players.